Literasi Media Sosial Sebagai Antisipasi Hoaks Bagi Organisasi Kemasyarakatan Muslimat NU di Kabupaten Demak - Ulya, Himmatul; Restu Ayu Mumpuni; Nugraheni Arumsari; Siti Muslikhatul Ummah (Universitas Negeri Semarang, 2025)
The internet use in Indonesia, particularly among women, has shown significant growth, with a penetration rate reaching 49.1% in 2024. However, this increase has not been matched by a corresponding rise in digital literacy, especially in discerning accurate information, which remains low among housewives. This is evident from various cases of hoax dissemination where women were the primary perpetrators. To address this issue, this community service initiative focuses on the Muslimat NU group in Sayung District, most of whose members are women over 45 years old and active on social media and messaging apps like WhatsApp and Facebook. This program aims to empower and improve the community's well-being by enhancing digital literacy through social media literacy, particularly in knowledge and competency for older women using social media. This group was selected because its characteristics reflect those of